2004
DOI: 10.1007/s00125-004-1349-z
|View full text |Cite
|
Sign up to set email alerts
|

Insulin expressing cells from differentiated embryonic stem cells are not beta cells

Abstract: Aim/hypothesis. Embryonic stem (ES) cells have been proposed as a potential source of tissue for transplantation for the treatment of Type 1 diabetes. However, studies showing differentiation of beta cells from ES cells are controversial. The aim of this study was to characterise the insulin-expressing cells differentiated in vitro from ES cells and to assess their suitability for the treatment of diabetes. Methods. ES cell-derived insulin-expressing cells were characterised by means of immunocytochemistry, RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
120
3
4

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(135 citation statements)
references
References 53 publications
8
120
3
4
Order By: Relevance
“…Based on these findings, recent studies have also suggested the potential of hESCs to differentiate into insulin-producing cells through spontaneous in vitro differentiation [5] or the use of a multi-stage protocol [6]. However, several studies have claimed that insulin staining of ESC-derived cells is likely due to insulin uptake by apoptotic cells from the culture medium [19][20][21], suggesting that more reliable analyses should be considered in terms of beta cell physiology and from an embryological standpoint. To date, many studies using mouse ESCs or hESCs have focused mainly on a relatively late phase of differentiation, rather than addressing the dynamics of differentiation from ESCs into pancreatic endoderm.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, recent studies have also suggested the potential of hESCs to differentiate into insulin-producing cells through spontaneous in vitro differentiation [5] or the use of a multi-stage protocol [6]. However, several studies have claimed that insulin staining of ESC-derived cells is likely due to insulin uptake by apoptotic cells from the culture medium [19][20][21], suggesting that more reliable analyses should be considered in terms of beta cell physiology and from an embryological standpoint. To date, many studies using mouse ESCs or hESCs have focused mainly on a relatively late phase of differentiation, rather than addressing the dynamics of differentiation from ESCs into pancreatic endoderm.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, using the same differentiation protocol, it was found that insulin immunoreactivity occurred as a consequence of insulin uptake from the medium [2], neuronal cells were formed [2][3][4], or insulin was released as an artefact from differentiated ES cells [2,3]. Functional pancreatic cells, however, were successfully generated using lineage selection strategies based on pancreas-specific promoters [5,6], by modified protocols in combination with transgene expression [7][8][9], or by addition of a phosphoinositol-3 kinase inhibitor [10].…”
mentioning
confidence: 99%
“…Despite these encouraging reports, some doubts have been raised regarding the evidence for de novo insulin synthesis [17][18][19]. Several protocols depend on the addition of supplemental growth factors and nutrients to the media in a serumfree step-one of these added factors is insulin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insulin staining alone has been found to exaggerate genuine differentiation toward a beta-cell type and subsequent studies have focused on immunoreactivity for C-peptide as a means of 'beta-cell' determination (C-peptide being a by-product of insulin biosynthesis). More recently, authors have reported that ES-derived populations expressing insulin, and in some cases C-peptide, are devoid of granules typically found in beta-cells and are mostly apoptotic [18] and that insulin is released artifactually from differentiated ES cells [19]. The presence of neuronal-like phenotypes within the differentiated ES cultures [18] and the suggestion that insulin-positive cells may be extra-embryonic in origin [20] has also highlighted the need for stringent criteria to define true beta-cell identity.…”
Section: Introductionmentioning
confidence: 99%